Kicz z importu? Wprowadzenie do odbioru i oceny japońskiej animacji - Jadwiszczok-Molencka, Helena; Molencki, Jacek (Załącznik Kulturoznawczy, 2016)
This paper delves into the meaning of kitsch in Japanese popular culture through the analysis of their esthetical and ethical values, as well as historical-religious context. It proves also the difficulties of studying the aforementioned culture because of the geographical remoteness of this country and different mentality of its people. The text shows the beginnings of Japanese animation, called ‘anime’ for short, its essential parts and the overall canon. The most important aspect of this work is finding the answer whether anime and all its related products are associated with kitsch, camp or should they be interpreted as something completely different.